ISLAM AND POLITICAL SCIENCES - Maarif, A Syafii (Jurnal Bestari, 1992)
wen Shaikh Ali Abd.al-raziq published his controversial book, al-islam wa usul al-hukkm (islam and the principles of goverment) in 1925, most of the Ulama out rightly  disseminating the poisonous political theory, completely dictated by western orientalists in order tu undermine Islam form wtihin. as we know, this egyptian author, an al-azhar garaduate, not only repudiated the shar;i based theory of the caliphate, but also stated that the prophet had no any political business.